Expression profiling analysis reveals key microRNA–mRNA interactions in patients with transposition of the great arteries and systemic left and right ventricles - Abu-Halima, Masood; Wagner, Viktoria; Rishik, Shusruto; Raedle-Hurst, Tanja; Meese, Eckart; Abdul-Khaliq, Hashim (Frontiers in Cardiovascular Medicine, 2023)
Background Patients with transposition of the great arteries (TGA) have different connected systemic chambers and this determines the long-term morbidities and survival. Limited findings have been reported to systematically identify miRNA and mRNA expression levels in such cohorts of patients. In this study, we aimed to characterize miRNAs, mRNAs, and miRNA–mRNA interaction networks in patients with TGA, with a systemic left (LV) and right ventricle (RV). Materials and methods Large panel of human miRNA and mRNA microarrays were conducted to determine the genome-wide expression profiles in the blood of 16 TGA-RV patients, 16 TGA-LV patients, and 16 age and gender-matched controls. Using real-time quantitative PCR (RT-qPCR), the differential expression level of a single miRNA was validated. Enrichment analyses of altered miRNA and mRNA expression levels were identified using bioinformatics tools. Results Altered miRNA and mRNA expression levels were observed between TGA-RV and TGA-LV patients, together or separated, compared to controls. Among the deregulated miRNAs and mRNAs, 39 and 101 miRNAs were identified as significantly differentially expressed in patients with TGA (both TGA-RV and TGA-LV) and TGA-RV, when compared to matched controls. Furthermore, 51 miRNAs were identified as significantly differentially expressed in patients with TGA-RV when compared to patients with TGA-LV. RT-qPCR relative expression level was highly consistent with microarray analysis results. Similarly, 36 and 164 mRNAs were identified as significantly differentially expressed in patients with TGA (both TGA-RV and TGA-LV) and TGA-RV, when compared to matched controls. Additionally, miR-140-3p showed a higher expression level in patients with overt heart failure (FC = 1.54; P = 0.001) and miR-502-3p showed a higher expression level in patients died due to cardiac death (FC = 1.41; P = 0.011). Integrative analysis resulted in 21 and 23 target genes with higher and lower expression levels, respectively (r ≥ 0.50 and P < 0.05). These target genes (i.e., 21 and 23 target genes) showed an inverse direction of regulation with miRNA and exhibited a miRNA binding site position within the 3′UTR of the target gene. Conclusion Our findings provide new insights into a potential molecular biomarker(s) for patients with TGA that may guide better risk stratification and the development of novel targeting therapies. Future studies are needed to investigate the potential significance of miRNAs and mRNAs in TGA-related cardiovascular diseases.